Diversity of Invertebrate Epifaunas Associating with Mangrove In Balangdatu Village Tanakeke Islands of South Sulawesi - Crisnawati Crisnawati; Magdalena Litaay; Dody Prisambodo; Slamet Santoso (International Journal of Applied Biology, 2017)
Research on the diversity of invertebrate epifaunas associating with mangroves in the Balangdatu village of Tanakeke regency, Takalar district, South Sulawesi, has been conducted from September to December 2016. The objective of this research was to know the diversity of invertebrate epifaunas associating with mangrove in Balangdatu Village of Tanakeke Islands. Sample collection was done by using explorative quantitatively plot methods with size 2 x 2 m, applied at three different stations. Data analysis includes calculation of Absolute density, Uniformity Index (Shannon-wiener), Dominance Index, and Distribution Index. The results showed that there were 13 species of epi fauna of 9 tribes, namely Littoraria sp 1, Cerithidea cingulata, Littoraria sp 2, Littoraria pallescens, Episesarma sp, Saccostrea cucullata, Pagurus sp, Terebralia sulcata, Cerithidea sp, Nerita planospira, Nisto histrio, Littoraria scabra, and Cassidula vespertilionis. The highest density was found in Littoraria scabra with a density of 0.72 ind/m2. Diversity indices are low which indicate depressed environmental conditions. Distribution Index values across stations <1 indicating that the pattern of individual dispersion tends to be uniform.